Air pollution control water heater by using paraffin wax from municipal wastes. (2020) - Sathish, T.; Subramanian, D. Bala; Muthukumar, K.; Karthick, S.
Abstract: The main aim of this study is to heat the water by burning the waste obtained from the houses and municipal wastes. The flue gases can be obtained by burning the wastes inside the furnace and then these flue gases can be treated with the help of the catalytic converter to remove the harmful gases such as CO, NOx, SOx. The treated flue gases will used to heat the phase change materials such as Paraffin wax then the heat obtained from the wax can be used to heat the water will be used during the night time. The municipal waste can be fed into the furnace at the top and free burning causes the fumes to heat the wax at 45 °C. (i.e.) the melting point of wax will in turn heat the water placed at the top by natural convection.